2018
DOI: 10.1159/000484236
|View full text |Cite
|
Sign up to set email alerts
|

miR-126 in Peripheral Blood Mononuclear Cells Negatively Correlates with Risk and Severity and is Associated with Inflammatory Cytokines as well as Intercellular Adhesion Molecule-1 in Patients with Coronary Artery Disease

Abstract: Objectives: The aim of this study was to evaluate the association of miR-126 with risk and severity of coronary artery disease (CAD) as well as its correlation with inflammatory cytokines and endothelial related proteins. Methods: In total, 215 patients suspected of CAD who underwent coronary angiography were enrolled in this case control study and were divided into a CAD group (n = 119) and control group (n = 96). miR-126 relative expression was assessed by real-time polymerase chain reaction. Results: The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…In addition, we also found that miR‐218 overexpression alleviated the inflammatory injury of CMECs damaged by CAD. MiR‐218 might negatively modulate HMGB1 expression in CAD inflammatory cytokines that are produced by monocytes, endothelial cells, or adipocytes, inducing or inhibiting the inflammation in diverse inflammatory diseases (Wu & Zhang, ). Besides, inflammation is a major factor for the pathogenesis of atherosclerosis, in which the inflammatory cytokines that are produced by macrophages or monocytes are pivotal triggers (Warnatsch, Ioannou, Wang, & Papayannopoulos, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found that miR‐218 overexpression alleviated the inflammatory injury of CMECs damaged by CAD. MiR‐218 might negatively modulate HMGB1 expression in CAD inflammatory cytokines that are produced by monocytes, endothelial cells, or adipocytes, inducing or inhibiting the inflammation in diverse inflammatory diseases (Wu & Zhang, ). Besides, inflammation is a major factor for the pathogenesis of atherosclerosis, in which the inflammatory cytokines that are produced by macrophages or monocytes are pivotal triggers (Warnatsch, Ioannou, Wang, & Papayannopoulos, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-126 has also been associated with the vascular smooth muscle cell (VSMC) turnover related to plaque thinning, and response to shear stress (Zhou et al, 2013). Recent investigations have demonstrated an association between CVD events and a decrement of miR-126 expression levels in different populations (Zampetaki et al, 2010;Fukushima et al, 2011;Kontaraki et al, 2014;Wu and Zhang, 2018). Zampetaki et al (2012), for example, found a decrement in the circulating miR-126 levels in individuals with type 2 diabetes compared to the control group Zampetaki et al (2012a).…”
Section: Plasma Mirnas Expression Levelsmentioning
confidence: 99%
“…One study showed that the AUC of miRNA-126 in diagnosing CAD was 0.98 ( 24 ). The predictive value of miR-126 for CAD may be explained by its essential roles in the mediation of endothelial cell activities and inflammatory responses ( 32 ). Moreover, miRNA-223 and miRNA-149 have relatively good potential as biomarkers for the diagnosis and prognosis of CAD patients, with diagnostic AUCs of 0.933 and 0.938, respectively ( 28 , 30 ).…”
Section: Discussionmentioning
confidence: 99%